Sumber Stres dan Coping Stress Pekerja dalam Masa Pandemi Covid-19 - Sudibyo Aji Narendra Buwana; Fendy Suhariadi; L. Rini Sugiarti (Ilmu Psikologi Universitas Yudharta Pasuruan, 2022)
The problem behind this is the source of stress and stress coping carried out during the pandemic of Covid-19. The purpose of this study is to explore the factors that are a source of stress and stress coping for workers during the pandemic of Covid-19. The method used in this study is a qualitative method. The subjects in this study were 7 workers as informant who worked in the National Strategic Project with characteristics that matched the criteria. The source of data and at the same time the method of data collection comes from primary data, namely data obtained from research subjects/informants through the results of questionnaires, interviews, and observations. In this study using research instruments in the form of questionnaires, observations and interviews. Data validation is done by doing triangulation. Data analysis techniques were carried out by means of data reduction, data presentation, and drawing conclusions. This qualitative research succeeded in answering the research objectives, namely successfully exploring the factors that became a source of stress and at the same time knowing the stress coping. The results obtained after the factors that are sources of stress are classified into two categories, namely sources of work-related stress and sources of stress that are not related to work. Researchers managed to explore 7 informant of stress related to work, 16 sources of stress that are not related to work and 12 coping stress. The conclusion of the study is to answer the research objective, namely to successfully explore the factors that are a source of stress and at the same time find out how to coping with stress.